Study on the Microscopic Mechanism of Spontaneous Combustion and Oxidation Kinetics of Water-Leached Coal - Naifu Cao; Gang Wang; Yuntao Liang (Journal of Chemistry)
In this article, a series of experiments have been carried out to study the spontaneous combustion and oxidation mechanism of coal after water immersion and investigate its tendency to spontaneous combustion, analyze the difficulty of spontaneous combustion of coal samples under different water immersion conditions, and establish a kinetic model of water immersion coal oxidation (taking the Bulianta 12# coal as a case study). They rely on physical oxidation adsorption, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), thermogravimetry, and oil bath heating. SEM has been used to analyze the characteristics of coal pore structure under different water immersion conditions (water-saturated coal samples under different water loss conditions until the coal samples are completely dried); FTIR served to investigate the characteristics of the molecular chemical structure of the coal surface before and after the coal is immersed in water. Through programmed temperature oxidation experiments combined with FTIR analyses and gas chromatographic (GC) analysis of gaseous products, it has been possible to study the changes of molecular structure and gas products on the surface of coal samples at different temperatures and water immersion conditions. The oxidation reaction rate of the 12# coal samples of Shendong Mine’s Bulianta Mine under different water content conditions during the spontaneous combustion process has been quantitatively studied. The difficulty of spontaneous combustion of coal samples has been correspondingly addressed. A kinetic model from the perspective of oxygen consumption has been proposed. Thermogravimetry-differential scanning calorimetry (TG-DSC) has been used to analyze and study the exothermal oxidation process before and after coal immersion. From the perspective of the exothermic intensity of the coal-oxygen reaction, an oxidation kinetic model for immersed coal samples has been developed to qualitatively determine its spontaneous combustion tendency. Results have shown that the increase in the specific surface area increases the risk of spontaneous combustion, and coal samples after soaking and drying have a stronger tendency to spontaneous combustion than raw coal. The moisture content of the coal sample leading to the easiest ignition conditions is 16.05%. Regardless of the moisture content, the critical temperature is maintained at 65–75°C, and the temperature of the left coal in the goaf should be prevented from exceeding this critical value.